1989
DOI: 10.1111/j.1439-0434.1989.tb04910.x
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium sporotrichioides Sherb., Fusarium tricinctum (Corda) Sacc. and Fusarium poae (Peck) Wollenw. — Cultural Characteristics, Toxinogenicity and Pathogenicity Towards Cereals

Abstract: Taxonomy, toxinogenicity and pathogenicity of 26 isolates of Fusarium‐Sporotricbiella section were studied. Strains of Fusarium sporotrichioides Sherb. isolated in Poland from cereals have been found severely pathogenic towards cereal seedlings. They produced significant amounts of T‐2 toxin (up to 600 mg/kg) and other trichothecenes under laboratory conditions. The investigated strains of F. tricinctum (Corda) Sacc. and F. poae (Peck) Wollenw. proved to be nonpathogenic and nontoxigenic under the same conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 10 publications
(6 reference statements)
0
10
0
Order By: Relevance
“…On the other hand E crookwellense showed relatively low pathogenicity to the cereals under study, in contrast to findings of Che/kowski et al (1988a) and Mafika (1989). E tricinctum referred as not pathogenic to cereal seedlings (Che/kowski et al, 1989;Marika, 1989) in our studies was found as a medium and/or weakly pathogenic, respectively. Mesterhazy (1987) stated that the cereal resistance to E culmorum and E graminearum should be considered at the genus and not at the species level, since the species specific resistance seems not to exist.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…On the other hand E crookwellense showed relatively low pathogenicity to the cereals under study, in contrast to findings of Che/kowski et al (1988a) and Mafika (1989). E tricinctum referred as not pathogenic to cereal seedlings (Che/kowski et al, 1989;Marika, 1989) in our studies was found as a medium and/or weakly pathogenic, respectively. Mesterhazy (1987) stated that the cereal resistance to E culmorum and E graminearum should be considered at the genus and not at the species level, since the species specific resistance seems not to exist.…”
Section: Discussionmentioning
confidence: 73%
“…E nivale) and E graminearum. Many other Fusarium species were isolated from diseased heads and kernels (Lacicowa, 1980;grobarova & Va~kova, 1987;Che/kowski et al, 1988b;Wilcoxson et al, 1988;Che/kowski, 1989;Adler et al, 1990;Arseniuk et al, 1991a, b).…”
Section: Introductionmentioning
confidence: 99%
“…including F. graminearum Schwabe (Snijders 1990;Parry et al 1995;Bourdages et al 2006), F. poae (Peck) Wollenw. (Parry et al 1995;Polley and Turner 1995;Bourdages et al 2006), F. avenaceum (Bourdages et al 2006), and F. sporotrichioides (Chelkowski et al 1989;Parry et al 1995;Bourdages et al 2006) (Weimer 1928) and root and wilt diseases of alfalfa and clover caused by F. oxysporum and F. avenaceum (Leath and Kendall 1978;Miller-Garvin and Viands 1994;Venuto et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Apical cell is curved and pointed, basal cell is notched or foot-shaped. The fungus is compared with taxonomically related species, which show the presence of polyphialides that produce pyriform as well as fusiform microconidia and blastospores (Chelkowski et al 1989). An important feature for their distinction from other fusaria is numerous brown and globose chlamydospores, which are thick-walled, filled with lipid-like material serving to carry the fungus over winter in soil when no suitable host is available.…”
Section: Resultsmentioning
confidence: 99%